2021: o ano da imunização? - Baroni, Daiana Paula; Alvarenga Filho, José Rodrigues de; Queiroz e Melo, Maria de Fatima Aranha de; Henriques, Victor Freitas (Revista Pesquisas e Práticas Psicossociais, 2021)
__